Lithium response in bipolar disorder: No difference in GADL1 gene expression between cell lines from excellent-responders and non-responders. (May 2017) - Moreira, Jeverson; Courtin, Cindie; Geoffroy, Pierre A.; Curis, Emmanuel; Bellivier, Frank; Marie-Claire, Cynthia,
Abstract: Previous association studies have shown mixed results between glutamic acid decarboxylase like-1 (GADL1) gene polymorphism and prophylactic lithium response in bipolar disorder (BD) patients. In the present study, GADL1 gene expression was investigated in regard to lithium response, using Alda scale, in lymphoblastoid cells (LCLs) of 36 Caucasian BD patients. No difference in GADL1 expression was observed among LCLs from excellent-responders, non-responders or controls. Furthermore, lithium did not induce significant changes in GADL1 expression levels after 4 or 8 days. These results did not support an association of GADL1 expression in the determination of a lithium response in BD patients. Highlights: In humans, the physiologic role of GADL1 requires clarification. Conflicting results have been obtained in genetic association studies between the GADL1 gene polymorphism and lithium prophylactic response. Lithium does not affect GADL1 gene expression in cell lines from BD patients.